2022
DOI: 10.3389/fmicb.2022.802292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Detection of Immunoglobulin G and Immunoglobulin M Antibody Against Spike Protein of SARS-CoV-2 by a Rapid Kit in a Real-Life Hospital Setting

Abstract: BackgroundAntibody testing is often used for serosurveillance of coronavirus disease 2019 (COVID-19). Enzyme-linked immunosorbent assay and chemiluminescence-based antibody tests are quite sensitive and specific for such serological testing. Rapid antibody tests against different antigens are developed and effectively used for this purpose. However, their diagnostic efficiency, especially in real-life hospital setting, needs to be evaluated. Thus, the present study was conducted in a dedicated COVID-19 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The genetic makeup of SARS-CoV-2 can be investigated using molecular techniques like NGS, enabling its discovery [174], and MA has been utilized for genotyping and the identification of agents that cause diseases like SARS-CoV-2 [175,176]. Additionally, COVID-19 can be detected using the ECLIA serological-based diagnostic methodology [177,178]. The number of chosen studies for these methodologies, however, hindered their inclusion in the meta-analysis because the meta-analysis requires at least five studies with a p-value of less than 0.05 [142].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic makeup of SARS-CoV-2 can be investigated using molecular techniques like NGS, enabling its discovery [174], and MA has been utilized for genotyping and the identification of agents that cause diseases like SARS-CoV-2 [175,176]. Additionally, COVID-19 can be detected using the ECLIA serological-based diagnostic methodology [177,178]. The number of chosen studies for these methodologies, however, hindered their inclusion in the meta-analysis because the meta-analysis requires at least five studies with a p-value of less than 0.05 [142].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular techniques such as NGS allow the investigation of the genetic composition of SARS-CoV-2, allowing its detection [182], and MA has been used for genotyping and the determination of agents that cause diseases such as SARS-CoV-2 [183,184]. Furthermore, ECLIA serological-based diagnostic technique is a valid detection method for COVID-19 [185,186]; however, the number of selected studies of these techniques prevented their inclusion in the meta-analysis, which needs at least five studies for analysis with a p-value lower than 0.05 [142]. In a search of individual MeSH terms for "COVID-19", "Sensitivity and specificity", "Next generation sequencing", "Microarray Analysis", and "Immunoassay" showed 195,931, 641,415, 49,966, 95,596, and 2,150 studies, respectively, while linking them only found 16, 3 and 367, correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SARS-CoV-2 virus in atmospheric air and contact surfaces in a COVID-19 dedicated hospital [4] was reported and the appearance of certain specific biochemical indicators such as the M-band(s), β-γ bridging, and pre albumin band signified that a rise in positive acute phase reactants occurred in COVID-19 [5] patients admitted to our hospital. Additionally, the detection of IgM against the receptor-binding domain (RBD) of S protein by the rapid test kit was found to be less effective, but IgG detection was reported as an effective diagnostic tool for SARS-CoV-2 infection [6]. Furthermore, research conducted by the biochemistry department, MAMC also came up with a conclusion that the exposed population in an endemic area of tuberculosis and typhoid is likely to withstand COVID -19 better with a reduced mortality [7].…”
Section: Significant Role Of the Biochemistry Departmentmentioning
confidence: 99%